Comparative study on emulsifying and physico-chemical properties of bovine and camel acid and sweet wheys. (March 2020) - Lajnaf, Roua; Trigui, Ines; Samet-Bali, Olfa; Attia, Hamadi; Ayadi, M.A.
Abstract: Main goal of this research was to examine the emulsifying properties of acid and sweet wheys extracted from bovine and camel fresh milks after heating at 70 and 90 °C for 30 min at laboratory scale. Specifically, emulsifying properties (emulsification stability (ESI) and activity (EAI) indexes) and the physico-chemical characteristics (surface hydrophobicity, ζ-potential, interfacial tension and denaturation rate) of wheys were assessed. Maximum EAI and ESI were found for sweet wheys (EAI 2 m 2 /g; ESI 65%), with higher EAI values for the camel whey. This behavior was explained by the strongest electrostatic-repulsive forces between oil droplets under conditions away from the isoelectric-point of proteins in agreement with the ζ-potential measurements. Findings indicate that heating affected the physico-chemical properties of camel and bovine whey proteins in acidic conditions by increasing surface hydrophobicity and the ability to reduce the interfacial tension. These results confirmed the protein-protein aggregation of heated acid wheys as proved by electrophoreses. Highlights: Emulsifying properties of whey proteins were highly influenced by heat treatment. Sweet camel and bovine wheys coated oil droplets better than acid wheys. The maximum Emulsion Activity Index values were observed for sweet camel whey. Heating significantly increased the emulsion stabilizing properties of acid wheys.